CFD modeling of bubble-induced turbulence - Rzehak, Roland; Krepper, Eckhard (International journal of multiphase flow, 2013)
•New proposal of source terms in k–ε model describing bubble-effects on turbulence.•Comparison of several models for bubble-induced turbulence.•Validation of the models with an experimental database.•Identification of suitable closure for bubbly turbulence.•Enables prediction of turbulent kinetic energy and dissipation including bubble effects. Modeling of bubble-induced turbulence in dispersed gas–liquid multiphase flow is an important but still unresolved issue. Aside from its intrinsic interest, turbulence in this type of flow has a strong impact on other important processes like turbulent dispersion of the bubbles and bubble-coalescence and -breakup and thus is a central part of the overall model. Especially the latter require as input values of turbulent kinetic energy and dissipation, which as shown subsequently are not readily obtained from the most common approach to add a bubble-induced contribution to the effective viscosity. This may be overcome by including source terms in the single phase two-equation turbulence models that describe the bubble effects on the liquid turbulence. However, no consensus on the precise form of these terms has been reached yet. We here report a comparison of different models of this type. Special care has been given to the selection of a rather comprehensive set of reference data allowing to qualify the validity of the different models. Conclusions towards best practice guidelines for modeling bubbly turbulence are drawn and needs for further research identified.